Cognitive workload management on globally interoperable network of clouds. (9th August 2019) - Morana, Giovanni; Mikkilineni, Rao; Keshan, Surendra
A new computing paradigm using Distributed Intelligent Managed Elements (DIME) and DIME Network Architecture (DNA) is used to demonstrate globally interoperable public and private cloud network deploying cloud agnostic workloads. The workloads are cognitive and able to adjust autonomously their structure and maintain desired quality-of-service (QoS). DNA is designed to provide a control architecture for workload self-management of non-functional requirements to address rapid fluctuations either in workload demand or fluctuations in available resources. Using DNA, a transaction intensive three-tier workload is migrated from a physical server to a virtual machine hosted in a public cloud without interrupting the service transactions. After migration, cloud agnostic inter-cloud and intra-cloud auto-scaling, auto- failover and live migration are demonstrated again, without disrupting the user experience or losing transactions.